The man from Barbarossa - Gardner, John E. (New York : Putnam, 1991)
James Bond has to stop the mastermind behind the Soviet terrorist group "The scales of justice" before they can unleash their horrendous plot.
Kirkus Review
Wilson's Fiction
Young Adult.
Young Adult
Keywords: Bond, James (Fictitious character) -- Fiction; Intelligence service -- Great Britain -- Fiction; Bond, James (Fictional character) -- Fiction; Spy stories